Rwanda Country Program Evaluation FY09-17 : An Independent Evaluation - Independent Evaluation Group (World Bank, Washington, DC, 2019)
The World Bank Group's positioning in relation to Rwanda's Vision 2020 goal of rapidly attaining Middle-Income Country (MIC) status reflected many of the elements that are critical to realizing the country's goal: (i) Under a first pillar of promoting economic transformation for sustained growth, it supported infrastructure (notably energy and transport); the business environment (including skills development); the financial sector (including rural finance); and in the latter years the urban sector. (ii) Under a second pillar of reducing social vulnerability and raising the productivity and incomes of the poor, it supported agriculture; health (initially); and social protection—including demobilization and reintegration of ex-combatants. (iii) A third accountable governance pillar aimed to strengthen central and decentralized public financial management (PFM). This evaluation assesses the development effectiveness of the World Bank Group's country program in Rwanda over the period FY09-17. The report aims to inform future partnership frameworks between the World Bank Group and the Rwandan Government. The report is also of interest to individuals and organizations working with countries striving to consolidate economic progress after a successful transition from conflict, or countries striving to reach middle-income country (MIC) status.